Strategies For Retaining Scarce Skills and Reducing Turnover in The South African Public Sector - Xolani Thusi; Richard Chauke (Research Synergy Foundation, 2023)
The South African public sector confronts a problem in retaining scarce skills because it competes in the labour market with the private sector, which provides higher packages/ benefits and conducive working conditions. Higher turnover of workers with scarce skills is a serious problem for service delivery and a costly exercise for the government. When scarce-skilled employees leave the public sector, vacant positions in the institutions' post establishments arise; as a result, the public institutions' ability to provide quality service delivery declines, and the recruitment and selection process is a costly process that further strains the government's budget. The capacity of a public institution to provide world-class service to its citizens is entirely dependent on the availability of competent staff who will carry out their tasks in such a manner that service delivery is enhanced. This paper aims to assess the current turnover rate among scarce skills employees within the South African public sector, and present viable alternatives for the government to address the escalating turnover issues, ultimately ensuring the retention of these valuable employees. To achieve the objective of the article, this paper used a review of the literature. The findings of this study revealed that the South African public sector is having difficulty attracting and retaining scarce skilled employees, which has a negative impact on the delivery and development of services. This higher turnover is faced by all levels of government and is driven by a competition for scarce skills between the government and the private sector, unfavourable working conditions, and less competitive packages, which has resulted in a situation where posts in the public sector remain vacant for longer periods of time. Few studies address concerns about scarce skills, high turnover, and personnel retention, particularly in the South African public sector. The author contends that this field should be further researched because effective and efficient public service delivery depends on the qualified staff.